Strategi Pencegahan Keterlambatan Pengembalian Dokumen Rekam Medis Rawat Jalan Poli KIA di Puskesmas Siliragung Kabupaten Banyuwangi - Novita Nuraini; Dewi Candra Agustin; Dony Setiawan Hendyca Putra; Indah Muflihatin (FORIKES, 2022)
According to the hospital's minimum service standards, the target for delays in returning medical record documents must reach 0% with 100% completeness of contents. The purpose of this study is to devise and implement strategies to prevent delays in returning medical record documents outpatient MCH poly. This type of research was qualitative using the PDCA method. The research subjects were medical record coordinators, medical record officers, MCH poly officers, DPJP, midwives, and heads of health center. Data were collected through interviews, observation, documentation studies, NGT and brainstorming. The validity test of the data was carried out by triangulating sources, time and techniques. The results of the research at the Plan stage were the identification of factors causing delays in DRM returns based on 5M, the man element, namely education that was still not in accordance with medical record qualifications, lack of knowledge of officers regarding DRM returns, lack of work experience due to a relatively new working period. The element of money was the insufficient budget for medical record facilities. The material element was that there are still incomplete DRM fillings. The machine element was that there were still problems with errors/slowness when inputting patient data on a computer/laptop, there was no telephone in the filing room, the use of expedition books was not optimal. The element of the method was that there was no SOP related to DRM returns and was also a priority problem with the proposed plan, namely making SOPs related to returning DRM and changing items in the expedition book. The do stage was carried out in April-May where before and after implementation there was a decrease. The Check stage had met the target so that the proposed planning activities could be continued in the action stage. The Action stage was validation and socialization regarding the SOP for returning DRM every month and optimizing the filling out of expedition books. It is recommended to optimize the filling out of expedition books, socialize SOPs every month, and evaluate the performance of officers.Keywords: PDCA; outpatient; medical records; public health center ABSTRAK Menurut standar pelayanan minimal rumah sakit, target keterlambatan pengembalian dokumen rekam medik harus mencapai 0% dengan kelengkapan isi 100%. Tujuan penelitian ini yaitu untuk menyusun dan melaksanakan strategi pencegahan keterlambatan pengembalian dokumen rekam medik rawat jalan poli KIA. Jenis penelitian yaitu kualitatif dengan menggunakan metode PDCA. Subjek penelitian yaitu koordinator rekam medis, petugas rekam medis, petugas poli KIA, DPJP, bidan, dan kepala puskesmas. Data dikumpulkan melalui wawancara, observasi, studi dokumentasi, NGT dan brainstorming. Uji keabsahan data dilakukan dengan triangulasi sumber, waktu dan teknik. Hasil penelitian pada tahap Plan adalah identifikasi faktor penyebab keterlambatan pengembalian DRM berdasarkan 5M, unsur man yaitu pendidikan yang masih belum sesuai dengan kualifikasi rekam medis, kurangnya pengetahuan petugas terkait pengembalian DRM, kurangnya pengalaman kerja akibat masa kerja yang terbilang baru. Unsur money yaitu anggaran dana yang kurang memenuhi untuk fasilitas rekam medis. Unsur material yaitu masih terdapat ketidaklengkapan pengisian DRM. Unsur machine yaitu masih terjadi kendala error/lemot saat input data pasien dalam komputer/laptop, tidak adanya telepon dalam ruang filing, kurang optimalnya penggunaan buku ekspedisi. Unsur method yaitu tidak adanya SOP terkait pengembalian DRM dan juga menjadi prioritas masalah dengan rencana usulan yaitu pembuatan SOP terkait pengembalian DRM dan perubahan item dalam buku ekspedisi. Tahap do dilakukan pada bulan April-Mei dimana sebelum dan sesudah pelaksanaan mengalami penurunan. Tahap Check telah memenuhi target sehingga usulan kegiatan perencanaan dapat dilanjutkan dalam tahap action. Tahap Action yaitu pengesahan dan sosialisasi terkait SOP pengembalian DRM setiap bulan serta pengoptimalan pengisian buku ekspedisi. Disarankan pengoptimalan pengisian buku ekspedisi, sosialisasi SOP setiap bulan, dan evaluasi kinerja petugas.Kata kunci: PDCA; rawat jalan; rekam medis; puskesmas